Benjamin Bailey and the Call for the Conversion of an Ancient Christian Church in India - McKee, Gary (2018)
Benjamin Bailey (1791-1871) was one of the first English-born Church Missionary Society missionaries to go to India. Along with Joseph Fenn and Henry Baker, Sr, he was part of what has been called the Travancore Trio. Their objective was to reform the ancient community of Syrian Christians in Travancore so that they in turn might be a great native missionary force in India. Their mission was known as the Mission of Help' to the ancient Syrian Church. The mission was distinctive from others in India at that time which sought more directly to call for the conversion of the country's massive Hindu and Muslim populations. This article will show that Bailey seriously underestimated doctrinal differences between the CMS and the Syrians. Moreover, the place of the Syrians in the complex social fabric of Travancore was not adequately understood. Unlike other missions, this one may almost be said to have as its aim the conversion of an existing church. That call for conversion, however, arose from fundamentally divergent understandings of Christian belief and practice. The article concludes by considering further some of the sources of these divergences and engaging with some of the critique that the mission of Help has received.
Keywords: Benjamin Bailey; CMS; India; Thomas Christians; Conversion